Atelier of sound - Ejdemo, Lis (My University, 2024)
This thesis investigates the interaction between architecture and sound, it addresses how sound is perceived within a spatial invention and during its travel through it. The project presents and explore different methods to influence sound waves by design, with the aim of tailoring the auditory experience. Through a multidisciplinary approach encompassing architecture, acoustics and phenomenology, the study seeks to answer the question: How can architecture influence, or modify, sound through the understanding of space, material and construction in a building dedicated for live performances of music? The investigation delves into two segments, materiality and form. It seeks to demonstrate the impact of each segment within the realm of acoustics and identifies tools to manipulate sound through thoughtful design and selection of material. To evaluate the impact of these segments, a study was conducted by measuring simulated sound in 3D-models. The outcome of the study identified optimal forms and materials for each space of the project. The architectural invention is situated at Sjöbergen in Gothenburg, located near the art museum Röda Sten. The rocky terrain, slow-paced river, and proximity to the city center present unique challenges and opportunities. The building’s design-narrative revolves around a central axis, serving as a backbone that leads visitors through a sequence of spaces, each offering different atmospheres. From the intimate spaces of narrow corridors to expansive openness of concert halls, the architectural transition unfolds. Moving down in the building the contrast between the light concert hall and the dark one reveals. Continuing out in the nature the visitor moves alongside the cliff and arrives to the amphitheater, the third and last space for music. The outcome of this thesis project unveils the relationship between sound and space. It critically reflects on designing without awareness of the sonic experience and highlight the responsibility an architect has on affecting the human behavior in the built environment.
Keywords: Acoustics, phenomenology, sound, music